Malaysia Airlines - Will the phoenix rise once more? - Mohd Zin, Syarizan Adzlinda (2009)
This dissertation seeks to digest the corporate culture theories and gauge if Malaysia Airline System’s (MAS) survival strategy after the 2005 turbulent will emancipate the company from current and future crisis. This research emphasizes on the correlation of the organisational performance culture-based strategy theories and the pursuit of competitive edge, which in this research assumption, is admissible to MAS. Hence, the most suitable approach seems to be a single case study method, arming with Business Turnaround Plan 1 (BTP1) and Business Transformation Plan 2(BTP2); the two major and powerful sources of reference. Subsequently, other related sources, which are directly linked to Malaysia Airline System (MAS) such as the previous case studies, company’s annual reports, newspaper reports, online materials as well as other relevant published sources to the Asia Pacific and global airline industry. Although MAS has granted its approval for this academic research, further interview request with it staff was unfortunately declined. The findings strongly suggest that the organisation’s performance is somewhat correlated with organisation’s culture and values, and that these elements shaped by the bold movement introduced by the management to maneuver the company after a deep crisis. The change into high performace culture helps to determine what sort of airline the organisation wants to become, as well as reducing the impact of external factors affecting the company. Interestingly, the study indicates not only high performance culture is an important determinant of success but also can help to accelerate and at the same time can impede the progress toward the goal. Strategy, culture and leadership must ultimately align and be synchronized. Attention to culture and successful efforts to shape it in support of holistic strategy to increase performance will surely separate the winners from the laggards.